Entrepreneurial Behaviour of Farmers in Imphal District of Manipur - Ram , Daya; Margaret, N.; Singh, M. K. (Indian Journal of Extension Education, 2014)
The present study was carried out in Manipur during 2013. Out of total nine districts in the state, Imphal West district was  selected keeping in view of highest population and population density. A proportional random sample was drawn from  each of 4 sub-divisions in the district. A sample of farmers comprising 100 respondents was selected from each sub division of the district based on stratified random sampling with proportional allocation method. Majority (66.00%) of the  agricultural and allied enterprises in Imphal District have medium extent of entrepreneurial behaviour followed by 18 per  cent of agriculture and allied enterprises that has low extent of entrepreneurial behaviour and 16 per cent of the  agricultural and allied enterprises had high extent of entrepreneurial behaviour. age, education, family size, socio economic status, sources of finance, sources of information, ability to coordinate enterprises activity and experience in  enterprises were to be positively and significantly correlated to extent of entrepreneurial behaviour of agricultural and  allied enterprises at 0.01 and 0.05 level of probability.
Keywords: Entrepreneurial behaviour; enterprises; variables